Inferential Models - Martin, Ryan; Liu, Chuanhai (Chapman and Hall/CRC, 2015)
A New Approach to Sound Statistical ReasoningInferential Models: Reasoning with Uncertainty introduces the authors' recently developed approach to inference: the inferential model (IM) framework. This logical framework for exact probabilistic inference does not require the user to input prior information. The authors show how an IM produces meaning.